2017
DOI: 10.1080/02678373.2017.1367736
|View full text |Cite
|
Sign up to set email alerts
|

Share, like, twitter, and connect: Ecological momentary assessment to examine the relationship between non-work social media use at work and work engagement

Abstract: Non-work social media use at work has seen a dramatic increase in the last decade and is commonly deemed counterproductive work behavior. However, we examined whether it may also serve as a micro-break and improve work engagement. We used ecological momentary assessment across one working day with up to ten hourly measurements in 334 white-collar workers to measure non-work social media use and work engagement, resulting in 2,235 hourly measurements. Multilevel modeling demonstrated that non-work social media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 56 publications
(69 reference statements)
2
69
0
2
Order By: Relevance
“…Finally, future research on workplace procrastination might also want to devote itself to further integrate the literature on workplace procrastination with other streams of work and organizational psychology literature, like the literature on withdrawal behavior (cf. van Eerde, 2016 ), task completion (e.g., Claessens et al, 2010 ), and online media use at work (e.g., Syrek et al, in press ). We have the impression that although procrastination is not quite often investigated in work settings, there are many related topics in work and organizational psychology that might benefit from a better inclusion of procrastination research and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future research on workplace procrastination might also want to devote itself to further integrate the literature on workplace procrastination with other streams of work and organizational psychology literature, like the literature on withdrawal behavior (cf. van Eerde, 2016 ), task completion (e.g., Claessens et al, 2010 ), and online media use at work (e.g., Syrek et al, in press ). We have the impression that although procrastination is not quite often investigated in work settings, there are many related topics in work and organizational psychology that might benefit from a better inclusion of procrastination research and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent meta-analytic evidence indicated that contrary to commonly held assumptions, cyberloafing did not negatively impact employees' job performance (Mercado, Giordano, & Dilchert, 2017). Other researchers have gone even farther and found that cyberloafing might have positive impacts such as elevating employees' moods (Lim & Chen, 2012) and increasing employee work engagement (Syrek, Kühnel, Vahle-Hinz, & De Bloom, 2018). Germane to the current study, researchers have also found that employees engage in cyberloafing in response to stressful work conditions (Henle & Blanchard, 2008;Pindek, Krajcevska, & Spector, 2018), providing initial evidence that cyberloafing may serve as one way for employees to cope with work stress.…”
Section: Introductionmentioning
confidence: 97%
“…When employees spend most of their time using SNSs, their mental ability to perform job‐related tasks is reduced, which results in low level of concentration required for the assigned job. According to Syrek, Kuhnel, Hinz, and De Bloom (), SNSs addiction reduces the work engagement of employees and distracts the essential energy required to perform the assigned tasks. Thus, SNSs addiction results in task distraction.…”
Section: Introductionmentioning
confidence: 99%